2001
DOI: 10.1097/00002030-200111230-00003
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal transmission of HIV-1 in hu-SCID mice: a new model for the evaluation of vaginal microbicides

Abstract: Because of its simplicity and practical features compared with other animal models, the vaginal HIV-infected hu-SCID mouse model may prove useful to test the activity of compounds against cell-associated HIV and, possibly, other sexually transmitted diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…However, our results strongly suggest that T lymphocytes cross the mucosal barrier and very rapidly disseminate in host tissues, including distant lymphoid tissues, where they can transmit infection to resident cells. Similarly, donor lymphocytes and monocyte/macrophages migrating across the cervico-vaginal mucosa and to distal lymphoid tissues have been reported in mouse models of reproductive physiology and infection [19][20][21][22].…”
Section: Discussionmentioning
confidence: 71%
“…However, our results strongly suggest that T lymphocytes cross the mucosal barrier and very rapidly disseminate in host tissues, including distant lymphoid tissues, where they can transmit infection to resident cells. Similarly, donor lymphocytes and monocyte/macrophages migrating across the cervico-vaginal mucosa and to distal lymphoid tissues have been reported in mouse models of reproductive physiology and infection [19][20][21][22].…”
Section: Discussionmentioning
confidence: 71%
“…Recently, Di Fabio et al (14) reported on the vaginal transmission of HIV-1 in hu-SCID mice as a new model for the evaluation of vaginal microbicides. This model turned out to be particularly useful to test the activity of compounds against cell-associated HIV, and therefore, should be highly relevant for the evaluation of compounds such as the lectins.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone is frequently used in vaginal infection models to synchronize estrous cycles and to increase susceptibility by thinning out the vaginal layer, including models of simian immunodeficiency virus/SHIV infection in nonhuman primates (13,14,67,69,70,78) and mouse models of HIV-1 (68,79), human papillomavirus (HPV) (80), and herpes simplex virus 2 (HSV-2) (81) infection. Increased susceptibility to viral infection after mucosal N-9 application has been described in models of HPV infection (80) and both vaginal and rectal HSV-2 infection (72,82,83).…”
Section: Discussionmentioning
confidence: 99%